Compressive Failure Behaviour of Kevlar Epoxy and Glass Epoxy Composite Laminates Due to the Effect of Cutout Shape and Size with Variation in Fiber Orientations - Mali, Mohamad; Azlan, Aina Atiqah; Mohammad Musa, Nur Nadhirah Syafiqa; Arifin, Siti Sufiah; Mahmud, Jamaluddin (International Journal of Integrated Engineering, 2022)
The increasing trend of constructing components made of composite laminates is due to the flexibility in tailoring their properties and high strength-to-weight ratio. Nevertheless, most practical components involve cutout features for fastening and these cutouts could reduce significantly the strength of the laminate. Due to its importance, many studies were conducted to study the effect of circular cutouts however, there is lack of information regarding the effect of various cutout shapes. Therefore, this study aims to investigate the compressive failure behavior of Kevlar Epoxy and Glass Epoxy composite laminates due to the effect of cutout shape and size with variation in fiber orientations. Finite element software, ANSYS were used to simulate the deformation and failure behavior of the laminates under compressive load. Prior to that, mesh convergence analysis and numerical validation were performed. Failure analysis was conducted for various cutout shapes (square cutout, diamond cutout, and circular) and size, based on Maximum Stress Theory. The results show that the existence of the cutouts on the composite laminates have reduced up to ten times the strength of the laminated composite plates. This information in regards to the failure behavior is important when designing components made of composite laminates under compression.